A Study on the Impact of Blue Light and Its Brightness on Long-Term Memory - Jin-Ho Kim; Kee-Sun Lee; Joung-Myo Shim; Chung-Won Lee (Applied Sciences)
The purpose of this study is to evaluate the effect of blue light and its brightness on long-term memory. Blue light was tested under four distinct illuminance conditions ranging from 400 to 1000 lux, and the results were compared with those of red light as a comparison group. A total of 25 individuals, including 16 men and 9 women with a mean age of 22.04 ± 1.74 years, participated in these tests based on a within-subject research design. Initially, each participant was exposed to individual light conditions for 30 min in the morning. Subsequently, they were asked to complete learning memory tasks, which involved memorizing specific words composed of randomly chosen English consonants. Exactly 20 min after these memory tasks, their long-term memory retention was measured through recall. It was found that blue light was superior to red light in terms of long-term memory enhancement; the difference was statistically significant, with a confidence level of 95%. Moreover, brighter light environments were found to affect long-term memory performance more significantly compared to darker light environments. That said, there was no significant difference in interaction effects between light color and brightness. These findings confirm the results of previous studies highlighting the effectiveness of blue light in enhancing memory retention while also demonstrating that the degree of enhancement may vary depending on light brightness.